A Review of the Book How Can Art Change Your Life? - Alireza Taheri; Batool Maazallahi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is an attempt to criticize “How Can Art Change Your Life” by Alain de Botton and John Armstrong. The foundations of this book rely on Dewey’s emphasis on restoring the link between the experience of aesthetics and ordinary life. According to Dewey’s pragmatic thought, if we put art away and then glorified it, or if we were only engaged in the task of choosing the great works of art, and merely reviewing them, we would have to understand the “role of art”. In civilization, we will be weakened. The authors of the book try to descend from the level of the description of art in a situation far from the experience of human life and formulate it in a practical and practical structure. By explaining the problems of the audience in dealing with art, they explain that art as a tool will be able to act as an effective tool against many of the hardships of the contemporary era, both in the private sphere and at the general level.